MỘT SỐ ĐẶC ĐIỂM SINH HỌC LOÀI CÁ HEO ÔNG SƯ (Orcaella brevirostris Gray, 1866) Ở VÙNG BIỂN QUẦN ĐẢO BÀ LỤA, KIÊN GIANG - Cù, Nguyên Định; Nguyễn, Thị Nga; L.M., Mukhametov; Bùi, Lai (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SEVERAL BIOLOGICAL CHARACTERISTICS OF IRRAWADDY DOLPHINS (Orcaella brevirostris Gray, 1866) IN BA LUA ISLANDS,KIEN GIANG PROVINCE In this document, we focus on the results of the 10 years Vietnam - Russia Tropical Center’s study on some biological characteristics of Irrawaddy dolphins (Orcaella brevirostris) which are in the IUCN Red List of threatened species in Vietnam. Several biological characteristics such as: shape, size, weight and anatomical features… of Irrawaddy dolphins (Orcaella brevirostris) in Ba Lua Islands, Kien Giang are defined. These are the first research results obtained in Vietnam for the purposes of the species conservation and development.